Environmental quality and animal welfare implications of commercial livestock transportation to slaughter facilities in North America: a review - Schuetze, Sarah Jane (Kansas State University, 2017)
There are several stressful events throughout an animal’s lifetime, but transportation is considered one of the most detrimental events to animal welfare by many professionals, regardless of species. Transportation consists of several different interacting and compounding factors that can affect animal welfare and meat product quality. The purpose of this report is to review current industry practices of land transport of different livestock types to slaughter facilities, primarily within the United States and Canada. This review evaluated species-specific transport practices and subsequent effects on animal welfare and carcass quality for both animal welfare and economic outlooks. Regulations are placed on the driver and time limits that the animals are allowed to be in transit. Trailer style use partially depends on the age and species of animal that is being hauled. Cattle are more likely to be hauled in pot belly trailers, while pigs are often transported in either pot belly or straight deck trailers. Poultry trailer type directly depends on the age of the birds being transported. Enclosed trailers are more often used in the European Union but are slowly making an impression on United States and Canadian markets. Cattle are transported several times in their lives with each trip varying in duration, loading density, and other environment altering factors. Each time the animals are transported there is the risk of low air flow, heat, or cold stress that can reduce animal welfare. Loading density has been broken down to equations, duration is limited by hours in trailer and location, and changes in physiology and behavior further exacerbate cattle transport stress. Pigs are transported fewer times than cattle, but thousands of pigs die during this process each year. Market weight pig mortality predictability increases with increasing temperature-humidity index and also increasing loading densities, with a specific equation to quantify this correlation. Shrink is another factor that can be linearly derived as transport time increases in swine. Fatigued Pig Syndrome is welfare issues that can impact the meat product resulting in pale, soft, and exudative pork. Poultry are usually only shipped once or twice and require special trailers and equipment. Shipping crates or modular drawers are used for grown birds where the birds are loaded into these containers, and then placed on a poultry trailer. Poultry have a very narrow comfort window of 21°C to 24°C, making transport difficult and detrimental to their welfare. Loading density is based on type and size of shipping container; however, regardless of loading density, the likelihood of bird death increases drastically as duration increases.
Keywords: Cattle; Livestock; Poultry; Slaughter; Swine; Transport